1967
DOI: 10.1002/path.1700940215
|View full text |Cite
|
Sign up to set email alerts
|

Some physiological characters of L forms of Staphylococcus aureus

Abstract: Cell membranes of Mycoplasma were isolated either by osmotic lysis or by ultrasonic disruption of the organisms. The membranes were dissolved in phenol-acetic acid-water (2:1:0.5, w/v/v), and membrane proteins were separated electrophoretically in polyacrylamide gels containing 5 m urea and 35% (v/v) acetic acid. The electrophoretic patterns of membrane proteins were highly specific for the different Mycoplasma strains examined. The use of this method to prove the identity or dissimilarity of Mycoplasma strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…When the loss of cell wall is obtained by means of growth on penicillin-containing media, several properties are reported to remain unchanged and only a few are lost or changed. Smith and Willis (19) have reported that L-forms of S. aureus resembled their original coccal forms in the qualitative production of catalase, coagulase, deoxyribonuclease, gelatinase, lipase, and colonial pigmentation; fibrinolysin and hemolysin could not be observed. Several authors also report that coagulase production is maintained in the L-forms (11,22).…”
Section: Resultsmentioning
confidence: 98%
“…When the loss of cell wall is obtained by means of growth on penicillin-containing media, several properties are reported to remain unchanged and only a few are lost or changed. Smith and Willis (19) have reported that L-forms of S. aureus resembled their original coccal forms in the qualitative production of catalase, coagulase, deoxyribonuclease, gelatinase, lipase, and colonial pigmentation; fibrinolysin and hemolysin could not be observed. Several authors also report that coagulase production is maintained in the L-forms (11,22).…”
Section: Resultsmentioning
confidence: 98%
“…Landman and Spiegelman (15) reported that high concentrations of nucleases were detrimental to the survival of protoplasts of Bacillus megaterium. However, L forms of S. aureus have been found to produce DNase (22), and so have protoplasts of group A streptococci (10).…”
Section: Discussionmentioning
confidence: 99%
“…The suspensions were disrupted by sonication (thirty 2-s bursts at 200–300 W with a 2-s cooling period between each burst) and then centrifuged at 10,000 × g for 20 min at 4°C. The supernatant was centrifuged at 100,000 × g for 1 h at 4°C to collect the cell membranes [34]. The cell membrane pellet was dissolved in resuspension buffer (10 mM potassium phosphate, 50 mM NaCl, 20% glycerol (v/v)) and stored at -70°C until use.…”
Section: Methodsmentioning
confidence: 99%